Multimedia Interaktif Untuk Pengenalan SOP Pengelolaan Limbah B3 Berbasis Android - Sabtu, Sabtu; Devega, Army Trilidia; Adi, Novi Hendri; Saputra, Benny (Universitas Lampung, 2022)
B3 waste is waste or waste which in its nature and concentration contains several toxic and hazardous substances which can directly or indirectly damage the environment, interfere with health, and threaten human survival. PT employees Jagar Prima Nusantara for B3 waste management SOP still use a notice board that contains SOP needed to carry out job desks at the company. So the authors designed an interactive multimedia application to introduce B3 waste management SOP at PT. Jagar Prima Nusantara which can be used on android smartphones. This study aims as a medium of information so that employees of PT. Jagar Prima Nusantara obtains information quickly and precisely. The design of the introduction of Android-based hazardous waste management SOP uses the Multimedia Development Life Cycle (MDLC) method which has six stages consisting of the concept, design, material collecting, assembly, testing, and distribution. At the design stage use storyboards, flowcharts, and UML. To implement what is used by the author using an application, namely Adobe Flash Professional CS6, and also at the alpha and beta testing stages using Blackbox. This research produces interactive multimedia based on Android, which is then distributed to companies. It is hoped that the application can improve the work performance of employees of PT. Jagar Prima Nusantara and make it easier for employees and customers to get the information they needKeywords: Multimedia Interaktif, Limbah B3, Android